The Intersection of Speech Surrogacy, Speech Melody, and Tonal- Drumming in Minangkabau Pasambahan Ritual Speech - Anton, Syahri -; Fulzi, Nadya -; Surayya, Yade -; Dary, Mohammad (Institut Seni Indonesia Padangpanjang, 2025)
This study examines the complex integration of speech substitute systemsin the traditional pasambahan (ceremonial speech) of the Minangkabaupeople of West Sumatra, Indonesia. Pasambahan is a highly structuredritual speech genre used in traditional ceremonies, characterized by itsmetaphorical language, specific prosody, and melodic contour (spokenmelody). The study hypothesizes that pasambahan not only employsparalanguage but also operates as a nuanced speech substitute, where itsstructured melodic patterns (spoken melody) and its codifiedrepresentation in talempong pacik (handheld gong) (pitched percussion)performances from complementary communication systems. Throughethnographic fieldwork and multimodal analysis of audio-visualrecordings of wedding and inauguration ceremonies in Luhak Nan Tigo,This study elucidates how the prosodic and melodic features of spokenPasambahan are systematically mapped onto the pitched percussionpatterns of talempong. These findings suggest that this tripartiterelationship between ritual speech, its inherent melody, and itsinstrumental substitute serves to enhance social status, reinforcecosmological concepts, and delimit ceremonial knowledge, therebyperpetuating socio-cultural authority. This research contributes to abroader theoretical understanding of speech substitutes by depicting theirmanifestation not in a stand-alone drum language but as embedded withinthe complex performative speech genre itself.